Research of the Biotope Diversity for the Purposes of Economic Valuation of Ecosystem Services in Chepelare Municipality (The Rhodopes Region of Bulgaria) - Assenov, Assen; Vassilev, Kiril; Padeshenko, H.; Koulov, Boian; Ivanova, Ekaterina; Borisova, Bilyana (European Journal of Sustainable Development, 2016)
The application of the philosophy or the management model for sustainable development has two main shortcomings – the condition of the global environment gets worse and the social inequalities deepen. Regardless of the integrity of UN Sustainable Development Goals 2030, the manifestation of the effect of the false demarcation between ecology and development continues. The integrated philosophy for sustainability and development is enriched with new terms, such as natural capital and ecosystem goods and services, while their assessment and evaluation is crucial for the achievement of sustainable development. The habitat, biotope and landscape diversity interpreted in GIS environment through evaluation of ecosystem goods and services in Chepelare Municipality is the main aim of the research, illustrated with maps of the biotopes, habitat types and landscapes. The obtained data through a GIS-based approach for evaluation and assessment of the ecosystem services is of high importance for the well-being of the municipality’s population. The results about the economic value of two main ecosystem services – wild fruits and herbs and genetic resources are comparable with results from other similar studies. An attempt is made for harmonization of information from different scales for examination – land cover classes with habitat types, biotopes and landscapes aiming at the precise evaluation of the interpreted ecosystem goods and services. Keywords: Biodiversity, biotope, habitat type, landscape biodiversity, environmental management, GIS.